2017
DOI: 10.17969/jtipi.v9i1.5976
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Bokasi dari Kotoran Berbagai Jenis Hewan

Abstract: Cow manure, different to other manures, has been frequently used as raw material of bokasi along with other organic waste materials such as sawdust, rice husk ash, and bran. This study aimed to utilize various livestock manures as one of the organic material in the production of bokasi. A completely randomized design with 2 replications was used in this study, which consisted of two factors: type of livestock manure (J) and proportion of livestock manure (P) of the total bokasi raw material.  Factor J consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…A research conducted [21] found that total microorganisms from the allocation of chicken and goat manure were higher than cow manure. This high amount shows the development of microorganisms which decomposited organic matters in goat manure better than cows.…”
Section: Number Of Leavesmentioning
confidence: 99%
“…A research conducted [21] found that total microorganisms from the allocation of chicken and goat manure were higher than cow manure. This high amount shows the development of microorganisms which decomposited organic matters in goat manure better than cows.…”
Section: Number Of Leavesmentioning
confidence: 99%
“…The difference in TCC that develops in each type of banana was due to differences in the nutritional content of each types of banana. According to (10), the calories, protein, fat, and b [10,7] ab [7,4] a [4,9] carbohydrates in awak bananas are higher than barangan and kepok bananas. Therefore, the higher the nutritional value of bananas, the more nutrients the microorganisms can use for their growth.…”
Section: Figurementioning
confidence: 99%
“…MOL is a microorganism that is used as a starter culture in production of organic fertilizers. The use of MOL as a biodecomposer in production of bokashi can accelerate the fermentation process (4). The advantage of using MOL is that it can be made from cheap materials or by utilizing agricultural waste with high fructose and glucose contents (5) so that it can increase the added value of waste and it can also reduce environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Kandungan N total tidak berbeda nyata untuk tiga kabupaten yaitu Kabupaten Kulon Progo. Sleman dan Bantul dan ketiganya lebih tinggi daripada Kabupaten Gunung Irfan et al (2017) menunjukkan bahwa kandungan N total dari kotoran sapi, kambing, dan ayam masing-masing adalah 0.4, 0.6, 1.0% lebih rendah daripada kandungan N dalam gulma siam. Kandungan N total untuk masing-masing kecamatan dalam setiap kabupaten, dan masing-masing desa dalam setiap kecamatan tidak berbeda nyata berkisar antara 1.84% di Kecamatan Panggang, Gunung Kidul dan 2.73% di Kecamatan Godean, Sleman.…”
Section: Kandungan Hara Gulma Siamunclassified